1969
DOI: 10.1083/jcb.43.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Surface Charge as an Explanation of the Recognition by Macrophages of Nuclei Expelled From Normoblasts

Abstract: The density and distribution of electric charge on the surface of rabbit bone marrow cells was visualized by electron microscopy after the cell surfaces had been stained with charged colloidal iron particles . Expulsed erythroid nuclei are less negatively charged than any other cell in the bone marrow . They carry from about one-half to one-third of the charge density on the remaining future reticulocyte . The reduction in the surface charge density is already apparent when the nucleus is partially expulsed . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
25
0

Year Published

1972
1972
1991
1991

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…Seno and others have suggested that macrophages have specific sites to recognize anionic groups on foreign substances, by which macrophages bind the substances to the surface and take them up into the cytoplasm (10,11,16,23,24,26,27). The general somatic cells may not have such binding sites.…”
mentioning
confidence: 99%
“…Seno and others have suggested that macrophages have specific sites to recognize anionic groups on foreign substances, by which macrophages bind the substances to the surface and take them up into the cytoplasm (10,11,16,23,24,26,27). The general somatic cells may not have such binding sites.…”
mentioning
confidence: 99%
“…The results were compared with our previous findings regarding the modulations of surface sialyl residues on the same ceils in rabbit (14,25,31) and in other mammalian species (15).…”
mentioning
confidence: 86%
“…specific saccharides (20, 21) and antigenic sites (7,22). Since, in most cell membrane glycoconjugates, sialic acid is attached either to a galactose or to an N-acetylgalactosamine residue (23,24), the masking and unmasking of these constituents are believed to be particularly important in the abovementioned interactions.We have shown previously that the differentiation and maturation of rabbit erythrocytes (RBC) are associated with striking modulations in cell surface sialic acids (14,25). These changes are expressed as a reduction in the density of sialyl residues after successive divisions of erythroid precursors.…”
mentioning
confidence: 99%
See 2 more Smart Citations